The Changes in Microstructure and Thermal Constant in Conversion of Carbonized Wood to Silicon Carbide Composite - Joko Sulistyo; Sri Nugroho Marsoem; Toshimitsu Hata (Masyarakat Peneliti Kayu Indonesia, 2015)
Carbonized wood which possesses microstructure with random orientation graphitic crystallites and with pores between the graphitic crystallites, is potentially developed into new material of silicon carbide (SiC) composite, a high performance material for engineering purposes. This paper investigates the development of the microstructure in the turbostratic carbon phase and the formation of SiC crystal from the reaction of carbon and SiO2. Results show the turbostratic microstructure in carbonized wood lead to the possible formation of SiC compound in the manufacturing of SiC/SiO2/Ccomposite. The heat treatment at 1800ºC on the mixture of SO2 and carbonized wood creates the formation of SiC compound, which improves the degree of microstructure ordering. The improvement of microstructure turbostratic carbon and the growth of graphitic crystallites in turbostratic carbon improves the thermal conductivity of SiC/SiO2/C composite comparingwith those of carbonized wood composite.